Integration Of Islamic Studies In English Language Teaching (Elt) Based On Study Program - Moh Mahmud; Ridwan, Ridwan; Ala Salsabila, Julanar; Hisam syafa'at, Muhammad (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
English is an agreed language as a world/international language, so this subject is a course or lesson that must be taken by all students and college students in Indonesia from elementary level to college as a compulsory course in the English Language Teaching (ELT) series. IAI Darussalam Blokagung Banyuwangi is a pesantren-based college campus, so the purpose of this research is to find out to what extent the educators integrate ELT with Islamic Studies in accordance with their study programs. The research method used is Descriptive Qualitative which determines the subjects of this study are several lecturers and students with data collection techniques prioritized from interviews and supported by observation and documentation. From the process in the field, it is found that the implementation of ELT which is integrated with Islamic Studies has been implemented even though it is still not totally, and this provides insight to students so that they can communicate about Islamic studies using English.